(untitled) (KULT_online, 2009)
John Paul II, Gandhi, Martin Luther King Jr., and Lady Di – disparate personalities who have one thing in common: The outpouring of collective mourning and broad media coverage that their deaths occasioned. This study in essay form by Hubertus Lutterbach, professor of ecclesiastical and cultural history at the University of Duisburg-Essen, takes as its departure point the cries of "Santo subito" at the burial of the last Pope and explores in-depth the media mechanisms of "popular sanctification." Lutterbach’s content analysis leads to the conclusion that the characteristics attributed to these "holy" idols closely resemble those of the medieval "man of God". Therefore, modern-day star worship can be regarded as an ongoing, secular manifestation of the medieval veneration of saints.